Anti-infective strategies in Pseudomonas aeruginosa biofilm formation - Kapoor, Priya (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2014)
P. aeruginosa infection is one of the main causes of lung function decline in patients with cystic fibrosis (CF). P. aeruginosa is associated with biofilm formation which can increase the rate of resistance to antibiotic treatment. Biofilms are communities of cells encased within an exopolysaccharide matrix. The overall aim of the project was to explore the activity of novel therapeutic agents against established P. aeruginosa biofilms.
Keywords: Clinical Microbiology, Ph.D.; Ph.D. Trinity College Dublin